Multilevel Computational Analysis of Fluorocarbon Polyatomic Deposition on Diamond - Devine, B.; Jang, I.; Kemper, T.; Lee, D.; Gale, Julian; Iordanova, N.; Simmott, S. (American Chemical Society, 2010)
Hyperthermal polyatomic fluorocarbon (FC) deposition upon the diamond (111) surface is simulated and analyzed at several levels of computational theory. Classical molecular dynamics simulations using the reactive empirical bond order (REBO) potential are used to categorize the surface reactions that occur during radical deposition. Molecular dynamics (MD) simulations, using density functional theory (DFT-MD) via the SIESTA method and program, are used to corroborate the findings from the classical simulations and to categorize reactions that occur during cation deposition. Finally, reaction enthalpies are calculated with higher level quantum mechanical methods using a cluster model to verify and refine the predictions from the MD simulations. The multilevel analysis predicts that FC radicals add directly to the diamond (111) surface with the simultaneous formation of HF. In contrast, FC cations preferentially dissociate H from the surface leaving behind a cationic carbon site. Cations and radical species are found to prefer different reaction pathways, which limits the applicability of REBO. Furthermore, the comparison reveals a difference in the predicted reaction probabilities between REBO and DFT which is attributable to the short cut off distance for interaction in the current REBO formulation.